Are arctic ungulates physiologically unique? - James M. Suttie; James R. Webster (Rangifer, 1998)
Reindeer/caribou (Rangifer tarandus) and muskoxen (Ovibos moschatus) are the arctic ungulates. Few studies have been carried out to directly compare their level of physiological uniqueness with similar species in the same family. The approach adopted in this review has been to compare data within family for physiological parameters including reproduction, nutrition and growth, to attempt to place the adaptations of reindeer/caribou and muskoxen in context. It is concluded that both species have unique adaptations to their environment which are likely to be specific to the Arctic. An hypothesis is advanced that some adaptations are constrained not only by the long intense winters, but also by the need to exploit the brief summers. The review has highlighted considerable gaps in understanding of some key physiological parameters for many species. This incompleteness in some ways mitigated the original goal of the project, but provisional conclusions are presented.